An assessment of solar irradiance enhancement events during CyCARE campaign at Limassol, Cyprus - Fragkos, Konstantinos; Fountoulakis, Ilias; Charalampous, Georgia; Papachristopoulou, Kyriakoula; Mamouri, Rodanthi-Elisavet; Ene, Dragos; Nisantzi, Argyro; Ansmann, Albert; Seifert, Patric; Hadjimitsis, Diofantos G.; Kazadzis, Stelios (My University, 2024)
Solar irradiance enhancement events, particularly under broken cloud conditions, can affect the Earth's energy balance and have direct implications for solar energy production and climate modeling. The ability to accurately quantify and understand these events can significantly contribute to improving our understanding of cloud-radiation interactions and, by extension, regional and global climate predictions. The Cyprus Aerosol and Cloud Experiment (CyCARE) campaign was an effort to elucidate aerosol-cloud interactions under the distinct dust and aerosol pollution conditions of the Middle East. Conducted in Limassol, Cyprus, from October 2016 to April 2018, as a collaborative endeavor between the Cyprus University of Technology (CUT) and the Leibniz Institute for Tropospheric Research (TROPOS). Utilizing the Leipzig Aerosol and Cloud Remote Observations System (LACROS) — a suite comprising both active and passive remote sensing instruments — the campaign facilitated an unprecedented collection of atmospheric data. Among these instruments, the PollyXT Raman-polarization lidar, 35-GHz cloud radar, disdrometer, Doppler wind-lidar, and microwave radiometer have been instrumental in capturing the vertical aerosol distribution, cloud microphysical properties, precipitation patterns, aerosol and cloud dynamics. A noteworthy aspect of the Cy-CARE campaign is the integration of the MObile RaDiation ObseRvatory (MORDOR) from June 2017, enhancing the measurement capabilities with a Class A pyranometer in compliance with ISO 9060:2018 standards for global horizontal irradiance monitoring. This study specifically aims to assess solar irradiance enhancement events attributable to broken cloud conditions observed during the Cy-CARE campaign. Leveraging the clear sky shortwave irradiance simulations from the radiative transfer package libRadtran, the research identifies and examines these enhancement events. Ancillary measurements of cloud evolution and microphysical parameters, courtesy of LACROS, furnish detailed insights into the cloud types instrumental in these enhancements.
Keywords: Clouds; Atmospheric modeling; Solar radiation models; Aerosols; Equipment; Data modeling; Environmental sensing; Remote sensing; Solar energy; Solar radiation; Atmospheric particles; Climatology